Effects of elasticity and waviness of the conductive panel surface on the cooling performance and entropy generation by using nano-enhanced multiple impinging jets - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2024)
The design of cooling systems is crucial for the thermal management of many energy systems including batteries, microelectro-mechanical systems, photovoltaics and many others. In this study, cooling system for elastic curved conductive panel is developed by using nano-enhanced multiple jet impingement. ALE finite element modeling of the entire coupled fluid-structure conjugate heat transfer system is employed for assessment, which considers both elastic flat and wavy panels. Type of the panel and operating parameters affect the cooling performance and entropy generation. Different effects and contributions of varying parameters such as Cauchy number (Ca), jet-cooling spacing (to the target plate and between the slots), wave amplitude and number of the conducive panel and nanoparticle loading amount in the pure fluid on the cooling performance and entropy generation features are analyzed. Increases in the Cauchy number, waveform amplitude, slot-slot distance, and slot-plate distance reduce the effectiveness of cooling, whereas increases in the nanoparticle loading have the reverse effect. When varying the Ca, there is 12.1% decrease of average Nusselt number (Nu) while average panel temperature rise becomes 3.1 & DEG;C by using nanofluid. The average Nu deteriorates by 7.7% and 6.6% when amplitude and wave number are varied while the corresponding temperature rises are achieved as 1.4 & DEG;C and 1 & DEG;C. When wavy and flat surfaces are used, using nanofluid provides 2.8 & DEG;C and 2.5 & DEG;C temperature drops. Lower entropy generation (EG) is obtained with flexible panel while higher amplitude of the wave form and increasing the nanoparticle amount result in EG reduction. The amount of EG reduction by using nanofluid becomes 21% and 27% at the highest loading.
Keywords: Elastic panel; entropy generation; finite element method; jet impingement; sinusoidal form